PEMANFAATAN LIMBAH AMPUL DALAM UPAYA MINIMASI LIMBAH PADAT (Limbah Benda Tajam) B3 MEDIS - Rahmi, Aulia; Fitrada, Wathri; Aziz, Rizki (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Medical waste is any type of waste containing infectious materials or infectious materials originating from health facilities. Medical waste management in Indonesia is still considered not optimal. Several categories or types of medical waste include infectious, pathological, radioactive, pharmaceutical, cytotoxic and sharps waste characteristics. Waste minimization is an effort to reduce the volume, concentration, toxicity (toxicity), and the level of danger that comes out of the environment by reducing the source or utilization of the waste itself. There is still little research on the minimization of medical waste. By collecting ampoules for one month as much as 502.898 grams and a total of 31.902 grams of sharps waste, the potential for ampoule waste minimization to sharps waste is 1.60%. Ampoules and Durham showed the same results in the presumptive and confirmatory tests for the presence of coliforms in the well, so the ampoules could be used as a substitute for Durham tube bacteria. ampoule waste in hospitals can be minimized, while for laboratories that perform MPN coliform meton testing can utilize ampoule waste so as to reduce the cost of purchasing Durham tubes.